Resource preferences and the emergence of individual niche specialization within populations. (19th July 2021) - Sol, Daniel; Lapiedra, Oriol; González-Lagos, Cesar; de Cáceres, Miquel
Abstract: Growing evidence that individuals of many generalist animals behave as resource specialists have attracted substantial research interest for its ecological and evolutionary implications. Variation in resource preferences is considered to be critical for developing a general theory of individual specialization. However, it remains to be shown whether diverging preferences can arise among individuals sharing a similar environment, and whether these preferences are sufficiently stable over time to be ecologically relevant. We addressed these issues by means of common garden experiments in feral pigeons ( Columba livia ), a species known to exhibit among-individual resource specialization in the wild. Food-choice experiments on wild-caught pigeons and their captive-bred cross-fostered descendants showed that short-term variation in food preferences can easily arise within a population, and that this variation may represent a substantial fraction of the population foraging niche. However, the experiments also showed that, rather than being limited by genetic or vertical cultural inheritance, food preferences exhibited high plasticity and tended to converge in the long-term. Although our results challenge the notion that variation in food preferences is a major driver of resource specialization, early differences in preferences could pave the way to specializations when combined with neophobic responses and/or positive feedbacks that reinforce niche conservation. Abstract : If you prefer some food types over others, you may end up specializing on the preferred foods. Using an experimental approach, we show that in pigeons preferences do not lead individuals to become resource specialists. While differences in food preferences can easily arise among individuals sharing the same environment, these differences are not biologically or culturally inherited from parents. As a result, they only last for short time periods and, in absence of mechanisms reinforcing preferences, this reduces the possibility of specialization.